IDENTIFYING MOTIVATORS OF ECOTOURISM DESTINATION COMPETITIVENESS: THE EXAMINATION ON SOFT INFRASTRUCTURE CONSTRUCTS AND MODERATING IMPACT OF MOBILE TECHNOLOGY - Chan, Wei Chiang; Lo, May Chiun; Wan Ibrahim, Wan Hashim; Mohamad, Abang Azlan; Thong, Jun Zhou (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2023)
The development of ecotourism in Malaysia is crucial in the current digitalized world, as nature enthusiasts seek authentic travel experiences to reconnect with the environment. This study focuses on investigating the link between government tourism policy, health services, safety and security, destination competitiveness, and the moderating effect of mobile technology. The study was conducted on 170 domestic tourists who visited various national parks in Sarawak, Malaysia. The data collected has undergone preliminary analyses using SPSS 26.0 while the proposed study model was evaluated using WarpPLS 8.0, which allowed for path modelling and bootstrapping to obtain the estimates of standard error and p-values. The results indicated a significant direct relationship between health services and destination competitiveness. Mobile technology was found to moderate the relationship between government tourism policy, safety and security, and destination competitiveness. However, due to the COVID-19 pandemic, the study was limited to domestic tourists, and the implications of these findings are discussed.